(untitled) (Journal of Education and Development, 2019)
Introduction: Medical students are motivated to engage actively in their studies. Yet at least 50% of medical students suffer from academic burnout. Using a social environmental perspective, this pilot study tested six hypotheses to account for medical student engagement and burnout via an effort-reward imbalance (ERI) model. Methods: This study measured ERI, over-commitment, engagement, burnout, negative affect, demographic variables, and test results during 2017. Seventy-nine medical students at a college of medicine in Seoul, Republic of Korea completed the online questionnaires (response rate: 20.73%). We used hierarchical regression analyses to examine the effects of ERI ratio, over-commitment, and the interaction between ERI ratio and over-commitment on engagement and burnout after adjusting for demographic variables and negative affect. Results: The ERI ratio was negatively related to engagement (p < 0.05), but over-commitment was positively related to engagement (p < 0.05). For burnout, affiliation, age, and negative affect were significant predictors. The ERI ratio was positively associated with burnout (p < 0.05). When we performed regression analyses on three sub-dimensions of engagement and burnout, the factors that affected each sub-dimension were different. Discussion: This pilot study revealed that the ERI ratio in school settings is a common factor for explaining the engagement and burnout of medical students. In addition, over-commitment significantly accounted for engagement, but it did not significantly account for burnout. These results for over-commitment may be explained by the unique characteristics of medical students.